Flushing intramedular dengan epinefrin pada prosedur Cemented Hip Arthroplasty menstabilkan mean arterial pressure tanpa mempengaruhi profil lipid - Aakash Aakash; Ketut Siki Kawiyana; I Wayan Suryanto Dusak; Ketut Gede Mulyadi Ridia; I Ketut Suyasa; I Gusti Ngurah Wien Aryana; I Gede Eka Wiratnaya; Anak Agung Wiradewi Lestari (Intisari Sains Medis, 2020)
Background: Cemented Hip Arthroplasty is the first choice of surgical treatment in fractures of neck femur and advanced hip osteoarthritis. Nevertheless, the complication, Bone Cement Implantation Syndrome can produce intra/postoperative mortality. The systemic effects of bone cement uses is hemodynamic disturbance and pulmonary embolism. These complications are thought due to the entry of semen particles into the systemic circulation caused by increased intramedullary pressure and local vasodilation. Intramedullary flushing with epinephrine after cement implantation is one of the interventions that is expected to reduce this impact. This study aims to determine the difference in hemodynamic effects and lipid profile in patients undergone flushing with epinephrine versus NaCl 0.9%.Methods: A cross-sectional study involving 30 patients who underwent Cemented Hip Arthroplasty, randomly divided into 2 groups. Surgical procedures differ only in the components used for intramedullary flushing, namely NaCl 0.9% (control) and epinephrine 1: 50000 (intervention). Vital signs are observed and recorded at minute 2,4,6,8, and 10 after cementation. Serial data were analyzed with repeated measures ANOVA. Lipid profile examination was performed before and 12 hours postoperatively and the results were analyzed with Wilcoxon-test.Results: The study observed a decreased of mean arterial pressure (MAP) in the control group after two minutes of cementation, and reached its lowest point in the sixth minute (p <0.05). In the intervention group, the decrease occurred in second to sixth minutes, but the decrease was more stable and there was no significant difference between time-point (p> 0.05). There were no significant differences of triglyceride and cholesterol level before and 12 hours after the procedure (p> 0.05).Conclusion: Intramedullary flushing with epinephrine after semen implantation in the Cemented Hip Arthroplasty procedure results in a minimal reduction of MAP compared to flushing without epinephrine. However, there were no difference in preoperative and postoperative cholesterol and triglyceride levels.Latar Belakang: Cemented Hip Arthroplasty menjadi pilihan utama terapi pembedahan pada fraktur collum femoris (Neck of Femur) serta osteoarthritis sendi panggul stadium lanjut. Meskipun demikian, komplikasi Bone cement implantation syndrome dapat menghasilkan morbiditas dan mortalitas intra/pasca operasi. Efek sistemik dari penggunaan semen tulang adalah gangguan hemodinamik dan emboli paru yang diduga akibat masuknya dari partikel semen ke sirkulasi sistemik akibat peningkatan tekanan intrameduler dan vasodilatasi lokal. Flushing intramedula dengan epinefrin paska implantasi semen merupakan salah satu intervensi yang diharapkan mengurangi dampak tersebut. Penelitian ini dilakukan untuk mengetahui perbedaan dampak hemodinamik dan profil lipid pada pasien dengan flushing epinefrine dan NaCl 0,9%.Metode: Penelitian potong lintang dengan melibatkan 30 pasien yang menjalani cemented arthroplasty, dibagi rata menjadi 2 kelompok secara acak. Prosedur pembedahan hanya berbeda pada komponen yang digunakan untuk flushing intramedula, yakni NaCl 0,9% (kontrol) dan epinefirn 1:50.000 (intervensi). Tanda vital diamati dan dicatat pada menit ke-2,4,6,8, dan 10 setelah sementasi. Data serial dianalisis dengan repeated measure Anova. Pemeriksaan profil lipid dilakukan sebelum dan 12 jam pasca operasi dan hasil dianalisis dengan Wilcoxon-test.Â Hasil: Penurunan mean arterial pressure (MAP) pada kelompok kontrol sejak menit ke 2 setelah sementasi, dan mencapai titik terendah pada menit ke 6 (p<0,05). Pada kelompok intervensi didapatkan penurunan terjadi pada menit ke 2 hingga ke 6, tetapi penurunan lebih stabil dan tidak terdapat perbedaan bermakna (p>0.05). Pada profil lipid (trigliserida dan kolesterol), tidak ditemukan perbedaan yang bermakna antara kadar sebelum operasi dan 12 jam setelah tindakan operatif (p>0,05).Kesimpulan: Flushing epinefrin paska implantasi semen pada prosedur Cemented Hip Arthroplasty menghasilkan penurunan MAP yang minimal dibandingkan flushing tanpa epinefrin. Akan tetapi, flushing epinefrin tidak memberikan perbedaan pada kadar kolesterol dan trigliserida paska operasi.